Marker Based Standardization of Himalayan Berry: Myrica esculenta Buch.-Ham ex D. Don - Shailajan, Sunita; Bhosale, Suhina; Menon, Sasikumar; Patil, Yugandhara (Asian Journal of Biological and Life Sciences)
Background: Myrica esculenta Buch.-Ham ex D. Don (Syn-M. nagi) commonly known as Himalayan berry/ Kaphal/ Katphal is an economically important medicinal plant with multipurpose uses. The medium sized tree is utilized for its bark, flowers, roots and fruits in Ayurvedic and Unani system of medicine due to its therapeutic potential. The fruits of M. esculenta are sold in local markets as jam, squashes, pickles etc and are also consumed by the local populations. However, the therapeutic properties of the fruits remain largely ignored. Objectives: The aim of this study is to develop standard quality control parameters and standardize the extracts of fruits of M. esculenta in terms of bioactive marker content and give it a recognition of a standardized extract before it becomes part of a herbal formulation. Materials and Methods: Standardization of fruits of M. esculenta has been carried out in terms of its pharmacognostic evaluation - physicochemical and phytochemical analysis. Chromatographic separation was achieved to develop the best resolved HPTLC and HPLC fingerprints as a quality control tool. Gallic acid, a bioactive marker, was quantitated from M. esculenta fruits collected from various regions of Uttarakhand, different morphological parts and from marketed formulation using validated HPTLC and HPLC method. Results: The LOD and LOQ levels were found to be 8 and 10μg/mL for HPTLC and 0.25 and 0.50μg/ mL for HPLC respectively with a linear response range of 10-500 μg/mL for HPTLC and 0.50-50μg/mL for HPLC. The (r2) was found to be greater than 0.99 using both techniques. The concentration of phytochemical marker varied in samples collected from different regions of Uttarakhand. Variation in the marker content has been also observed from different morphological parts and in marketed formulation. Conclusion: To attain reproducible quality of herbal products selection and use of authentic plant material is of utmost need. Unique fingerprints can be used as a quality control toolfor the use of authentic sample of M. esculenta singularly and as a part of various medicinal formulations. The method developed for the estimation of gallic acid can be applied to matrices containing M. esculenta fruits. The findings of the study will enable sustainable harvest of M. esculenta fruits and its processing as a value-added minor forest produce of Garhwal Himalayas.
Keywords: Fruits; Gallic acid; HPTLC; HPLC; Myrica esculenta; Validation.